2014
DOI: 10.1093/nsr/nwu014
|View full text |Cite
|
Sign up to set email alerts
|

PIWI proteins and their interactors in piRNA biogenesis, germline development and gene expression

Abstract: PIWI-interacting RNAs (piRNAs) are a complex class of small non-coding RNAs that are mostly 24–32 nucleotides in length and composed of at least hundreds of thousands of species that specifically interact with the PIWI protein subfamily of the ARGONAUTE family. Recent studies revealed that PIWI proteins interact with a number of proteins, especially the TUDOR-domain-containing proteins, to regulate piRNA biogenesis and regulatory function. Current research also provides evidence that PIWI proteins and piRNAs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
135
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(137 citation statements)
references
References 163 publications
(302 reference statements)
2
135
0
Order By: Relevance
“…At this time, our suggestion that Piwi-bound RNA is required for PHeMAAH is based solely on extrapolation of published evidence detailing Piwi-piRNA interactions (Le Thomas et al 2013;Mani and Juliano 2013;Ku and Lin 2014). We can only speculate on the identity of Piwi-associated RNAs that might be involved in PHeMAAH and whether these might be mature piRNAs or unprocessed nuclear transcripts.…”
Section: A Model For Hp1a-piwi Interaction In Phemaahmentioning
confidence: 95%
See 2 more Smart Citations
“…At this time, our suggestion that Piwi-bound RNA is required for PHeMAAH is based solely on extrapolation of published evidence detailing Piwi-piRNA interactions (Le Thomas et al 2013;Mani and Juliano 2013;Ku and Lin 2014). We can only speculate on the identity of Piwi-associated RNAs that might be involved in PHeMAAH and whether these might be mature piRNAs or unprocessed nuclear transcripts.…”
Section: A Model For Hp1a-piwi Interaction In Phemaahmentioning
confidence: 95%
“…A member of the Argonaute protein family, Piwi is able to bind piRNAs and repress the mobilization of retrotransposons within the germline (Mani and Juliano 2013;Ku and Lin 2014). However, Piwi is also a recognized binding partner of HP1a (Brower-Toland et al 2007), plays a role in the establishment of heterochromatin during early embryogenesis (Gu and Elgin 2013), and is required for pairing-sensitive silencing (Grimaud et al 2006), a phenomenon that involves crosstalk between homologous chromosomes (Kassis 1994;Americo et al 2002).…”
Section: Piwi Protein Stably Associates With Oocyte Chromosomesmentioning
confidence: 99%
See 1 more Smart Citation
“…1). Despite the relatively far phylogenetic distance, evidence for the majority of well-known fly and mammalian piRNA components (Ku and Lin 2014) could be found in the M. lignano genome and transcriptome (Supplemental Table 1). This suggests that a canonical piRNA pathway is likely to be operating in M. lignano.…”
Section: Macrostomum Lignano Has Conserved Small Rna Pathway Componentsmentioning
confidence: 99%
“…The primary function of piRNAs in bilaterians appears to be to silence of transposons within the germline (O'Donnell and Boeke 2007), however somatic piRNAs (Ross et al 2014) and piRNAs that function in mRNA translational control have also been identified , Saito et al 2009, Ku and Lin 2014.…”
Section: Rhoadesmentioning
confidence: 99%